A maldade humana na obra Ensaio sobre a cegueira de José Saramago a partir de uma perspectiva psicanalítica - Santana, Marcos Celso Prado (2023)
The connection between psychoanalysis and literature is historical and advantageous, being present in both, in different ways and methods, the motivation in the description and the unveiling of the mysteries of the human soul. This research aims to carry out a freudian psychoanalytic investigation on human evilness from the novel Ensaio sobre a cegueira, investigating specific aspects of the broad spectrum that constitutes human evilness. The novel Ensaio sobre a cegueira, by José Saramago, based on the fictional account of an event in which unnamed characters lose their sight, offers us a portrait of humanity when deprived of one of its main senses and how much such loss modifies social relationships and society itself. Emphasis will be given to the psychoanalytical concepts of narcissism, masochism, sadism and death drive and their articulation with aggressiveness, cruelty and violence, observing their presence and development in Ensaio sobre a cegueira and its connection with question of human evilness.